Capacity building in nonprofit sport organizations: Development of a process model. Issue 4 (August 2016) - Millar, Patti; Doherty, Alison
Highlights: Considerable gaps exist in the understanding of organizational capacity building. A process model of capacity building is proposed for nonprofit voluntary organizations. Organizational needs, readiness, strategies and outcomes of capacity building are discussed. Model provides theoretical foundation for examining successful capacity building. Model is described in the context of community sport organizations, but is intended for broad application. Abstract: Despite the growing literature on organizational capacity in nonprofit and sport organizations, considerable gaps remain when the analysis shifts to building that capacity. This study proposes a comprehensive model of capacity building that recognizes the concepts and relationships involved in that process. The model was developed according to de Groot's (1969) interpretative-theoretical methodology, consisting of four phases that guide the collection and review of relevant literature: exploration, analysis, classification and explanation. As a comprehensive process, effective capacity building acknowledges that a capacity needs assessment occurs in response to some environmental stimulus. The subsequent identification of specific objectives for capacity building is followed by the generation and selection of a strategy(s) and consideration of multiple aspects of readiness to build capacity. The short-term impact and long-term maintenance of built capacity must be assessed following the implementation of the strategy(s) to build, with consideration of the implications for program and service delivery that address the initial stimulus. The model is described in the context of community sport organizations, however it is intended for broad application. Concepts and relationships presented in the model are relevant to the nonprofit voluntary organizational setting in general, while allowing for contextualization based on the unique factors and influences that may be involved in the process of building capacity. The paper concludes with consideration of how the model may be used in practice and directions for future research.